A scar that cycles: unmasking episiotomy site endometriosis: a case report - Ghorpade, Niteen; Rahane, Tushar; Sinha, Anuvi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Endometriosis is a condition characterised by occurrence of endometrial cells outside the uterine cavity and when it appears at the previous scar site like episiotomy scar, caesarean scar or laparoscopic port incision scar sites, it is called extrapelvic or cutaneous endometriosis. Here we present a case of 31-year-old lady who had vaginal delivery with episiotomy scar 6 years ago. She presented at our center with cyclical pain at the episiotomy scar site and a hard nodular mass of 3×4 cm was found at the episiotomy site. She underwent complete excision of mass after thorough examination and imaging. The hsitopathology report confirmed the diagnosis. Hence, we knew that the definitive treatment of episiotomy scar site endometriosis is surgical and medical management has no role.